Microvascular mural cell organotypic heterogeneity and functional plasticity - Holm, Annegret Elisabeth; Heumann, Tina; Augustin, Hellmut (Trends in cell biology, 2018)
Microvascular mural cells (MMCs), comprising pericytes and microvascular smooth muscle cells, are of increasing interest in multiple fields of research for their plasticity and their organotypic functional roles in microvascular homeostasis and disease. They have been described as a heterogeneous cell population constituting a continuum of cell phenotypes along the microvascular bed with vascular smooth muscle cells (VSMCs) at one end of the spectrum and pericytes at the other end. MMC organotypic subpopulations have been suggested to function in a tissue-context-dependent manner, thereby contributing to organ-specific functional roles. However, the phenotypic and organotypic heterogeneity as well as their origin and marker identification are hitherto poorly defined. Here we review recent work and emerging concepts regarding MMC phenotypic and organotypic heterogeneity and their functional plasticity in health and disease.